1973
DOI: 10.1002/ps.2780040109
|View full text |Cite
|
Sign up to set email alerts
|

Endosulfan residues on alfalfa hay exposed to drying by sunlight, ultraviolet light and air

Abstract: Endosulfan residues on alfalfa hay exposed to drying by sunlight, ultraviolet light and air under controlled conditions were investigated using g.l.c. and t.l.c. Maximum loss of total endosulfan and related residues calculated as endosulfan occurred approximately 7 days after application and exposure on Lot 1 (dark) and 5 days on Lot II (ultraviolet light) and 6 days on Lot III (sunlight). Maximum losses of residues on Lot I, Lot II and Lot HI were 48.3, 66.7 and 81.9%, respectively. No endosulfan lactone was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1976
1976
1976
1976

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Fahey et al (1970) showed that carbofuran residues on green alfalfa were not found 14 days after treatment at the rates of 0.5 and 1.0 lb/acre in 20 gal of spray in Indiana, and dehydration of the alfalfa in a drum-type commercial dehydrator reduced the carbofuran residues by 65%. The effect of drying harvested mature alfalfa plants by sunlight, ultraviolet light, and air in the dark on residues of DDT and related chlorinated hydrocarbon residues (Archer, 1969), toxaphene residues (Archer, 1971), and endosulfan residues (Archer, 1973) has been published.…”
mentioning
confidence: 99%
“…Fahey et al (1970) showed that carbofuran residues on green alfalfa were not found 14 days after treatment at the rates of 0.5 and 1.0 lb/acre in 20 gal of spray in Indiana, and dehydration of the alfalfa in a drum-type commercial dehydrator reduced the carbofuran residues by 65%. The effect of drying harvested mature alfalfa plants by sunlight, ultraviolet light, and air in the dark on residues of DDT and related chlorinated hydrocarbon residues (Archer, 1969), toxaphene residues (Archer, 1971), and endosulfan residues (Archer, 1973) has been published.…”
mentioning
confidence: 99%